Analysis of Moral Values of Being in The Pursuit of Happyness Movie - Sonia Isabella; Eusabinus Bunau; Eka Fajar Rahmani (Kirana Publisher (KNPub), 2024)
This research aimed to analyze the moral values representing the educational values presented in the film